Sustainable eating lifestyle of selected young urban professionals in Metro Manila: Meaning, relevance, and signification - Godinez, Lounelle J. (Animo Repository, 2021)
This study describes the sustainable eating lifestyle of ten (10) Filipino Young Urban Professionals (YUPs), ages twenty (20) to thirty-five (35) living in Metro Manila. The research aims to describe YUPs experience in practicing sustainable eating lifestyle, founded on their philosophies and relative to their meaning, relevance and signification that impacts their everyday realities. This qualitative descriptive research utilized purposive sampling of convenience methods and used an online interview, with a researcher-administered interview guide used as data collecting tool. The research found that there is an analogous function with the sustainable eating lifestyle of the young urban professionals on the concept of habitus as conceived by Bordieu. These are reflected in their resilience, drive to share information, building their own community and by using sustainability as a philosophy. It is recommended that further studies on different age brackets be performed to examine their philosophies and a quantitative research to further analyze the emerging themes of this research.